Cases on collaboration in virtual learning environments processes and interactions - Russell, Donna 1955- (Premier reference source, 2010)
"Using a case study analysis, this book provides a unifying perspective for discussing the viability of collaborative virtual spaces as training programs for insurance brokers, forums to support at-risk university students, simulations of historical places, means to aid autistic children learn social skills, repositories for digital libraries, collaborative spaces designing new university programs and emergency response training" - Provided by publisher